Lysinibacillus sphaericus as species and biotechnological agent : a genomic review (2017)
This thesis can be considered the final part of a great project conducted by the CIMIC since 2013 with the first whole genome sequencing of a Colombian strain of Lysinibacillus sphaericus. Such a project was aimed at gaining a comprehensive understanding of L. sphaericus in the light of genomics. This has been studied in the CIMIC because of its promising use in biocontrol and bioremediation. The first part of the current document (Theoretical framework and Objectives) defines the main concepts involved in the biotechnological potentials of bacteria, focusing on the case of L. sphaericus and its promising potential applications for biocontrol and bioremediation. In addition, the controversy over the species circumscription of L. sphaericus is reviewed. Lastly, this section describes the state of the art and establishes the objectives of the current study. In Chapter 1, the parameters and results of the genome sequencing of the entomopathogenic strains 2362 and OT4b.49 are described. Results from these genome sequencing are compared to the current available L. sphaericus genomes on the NCBI Genome database. In Chapter 2, the species circumscription of L. sphaericus is discussed. A new bacterial species made up of the toxic strains is suggested. This propose is supported by the genomic data obtained in this study and by the experimental evidence previously reported in the scientific literature. In Chapter 3, a metabolic reconstruction of the L. sphaericus toxic strains is presented. This reconstruction was built from the obtained genomic data and offers a guideline for further studies on the biotechnological implementation of L. sphaericus. Finally, the last part of this document shows the Concluding remarks of the current work, including the questions about the L. sphaericus biology that remains unanswered. The Appendices section contains some unpublished results and other supplemental material that bolsters the hypotheses proposed herein.